2007
DOI: 10.1080/10426500601142114
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactions of Some Novel Quinoxalines for Anticancer Evaluation

Abstract: derivatives 5 and 6 were prepared, which, upon reacting with different reagents, afforded the triazolo, tetrazolo, and amino quinoxaline derivatives. Compounds 5, 8b, 9, 10b, and 11b were evaluated for their anticancer activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…On the other hand, it has been reported that a wide range of Schiff's bases with their reactive azomethine linkage shows interesting inhibitory activity against experimental tumor cells [5][6][7][8]. It is also suggested that the Schiff's bases could be hydrolyzed selectively by the tumor cells to act as alkylating agents at the same time as the active amine becomes free to act as antimetabolite [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that a wide range of Schiff's bases with their reactive azomethine linkage shows interesting inhibitory activity against experimental tumor cells [5][6][7][8]. It is also suggested that the Schiff's bases could be hydrolyzed selectively by the tumor cells to act as alkylating agents at the same time as the active amine becomes free to act as antimetabolite [9].…”
Section: Introductionmentioning
confidence: 99%
“…Quinoxaline-2-one derivatives are particularly interesting since some of them showed a variety of pharmacological properties, such as antimicrobial (Ajani et al, 2010;El-Sabbagh et al, 2009;Sanna et al, 1998;Sanna et al, 1999), antiviral (Xu et al, 2009), antifungal (Carta et al, 2002;Ingale et al, 2007;Sanna et al, 1999), anxiolytic (Ulrich et al, 1998), analgesic (Ingale et al, 2007), antiinflammatory (El-Sabbagh et al, 2009), antithrombotic (Ries et al, 2003;Willardsen et al, 2004), and antitumor (Hirai et al, 2011;Koth et al, 2007;Lawrence et al, 2001;Meyer et al, 2006) activities. Based on the computer modeling and "in vitro" studies, quinoxalin-2-ones have been proposed as potential drugs in treatments of various diseases (Carta et al, 2006).…”
mentioning
confidence: 98%
“…This amide-iminol tautomerism involves a fast hydrogen transfer between nitrogen and oxygen and these compounds usually exist in the predominant amide form [24][25][26][27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%